NARRATIVE WARS IN FAMILY LAW: DECONSTRUCTING MYTHS ABOUT PARENTAL ALIENATION IN BRAZIL AND THE WORLD (Editora Impacto Científico, 2025)
This article aims to critically analyze the Parental Alienation Law (Law No. 12,318/2010), deconstructing the narrative that associates it with the discredited "Parental Alienation Syndrome" (PAS). The methodology employed is a qualitative approach based on a critical analysis of the literature, hermeneutic dogmatics, and a comparative law study, focusing on decisions from international courts, such as the European Court of Human Rights and higher courts in the Americas. The results show that the Brazilian legislation, by focusing on "acts" of alienation, aligns with global best practices, which also concentrate on the alienator's abusive conduct and the protection of the child's best interest, rather than on a pathological diagnosis. The jurisprudential analysis confirms that the phenomenon is universally recognized and combated by the courts. Additionally, the study points out, from a methodological critique, the fragility of research that attributes a gender bias to the law, showing that the national legal system already has safeguards against its misuse in contexts of domestic violence. It is concluded that the Brazilian law is an advanced and constitutionally valid instrument, whose misinterpretation, not its text, fosters controversies, making its correct application essential for the protection of family life.DOI: https://doi.org/10.56238/edimpacto2025.084-004